Casting Equipment Engineering Guide - Nath, Jagan (Ohio : ASM International, 2023)
"The purpose of this book is to highlight all aspects of the entire line of equipment involved in the preparation and production of iron, steel, and aluminum castings, and their distinguishing features and innovations for higher productivity, higher dimensional capability, high integrity, and cost competitiveness. The book also offers guidelines for the selection of the right equipment, and for positioning them suitably, ensuring smooth product flow with high productivity. This practical guide should be of special interest to all those involved in the casting manufacturing engineering field and those who are engaged in new equipment purchases, expansions, modifications, and automation of new machinery. Casting buyers and purchasing managers would also find this guide very useful"--
Keywords: Casting